2019
DOI: 10.1021/acs.est.9b03296
|View full text |Cite
|
Sign up to set email alerts
|

UV-Improved Removal of Chloride Ions from Strongly Acidic Wastewater Using Bi2O3: Efficiency Enhancement and Mechanisms

Abstract: Strongly acidic wastewater generated from nonferrous metal smelting industries can be recycled as sulfuric acid after the contaminants have been removed, and among which, Cl– is rather difficult to remove. Although previous studies showed that Cl– can be removed from acidic Zn electrolyte by Bi2O3, this method still suffers from low efficiency when being employed for strongly acidic wastewater recycling. Otherwise, very high Bi2O3 dosage and H2SO4 concentration are required, leading to the need for improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The exploitation of photocatalysts is one of the keys to realize the high‐performance application of photocatalytic technology 10‐12 . Up to now, various semiconductor photocatalysts have been developed, including metal oxides (TiO 2 , Bi 2 O 3 , etc), 13‐16 metal sulfides (MoS 2 , Bi 2 S 3 , etc), 17‐21 multi‐component oxides (Bi 2 WO 6 , SrTiO 3 , etc), 22‐25 metal selenides (MoSe 2 , CdSe, etc), 26‐29 metal phosphides (Co 2 P, Ni 2 P, etc), 30‐32 metal phosphates (Ag 3 PO 4 , BiPO 4 , etc), 33,34 metal halides (AgBr, etc), 35‐37 metal oxyhalides (BiOBr, BiOCl, etc), 38‐40 metal‐free materials (SiC, g‐C 3 N 4 , etc) 41‐43 and so on. Among them, the semiconductor with a band gap of Eg ≥ 3 eV are called wide‐band‐gap photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of photocatalysts is one of the keys to realize the high‐performance application of photocatalytic technology 10‐12 . Up to now, various semiconductor photocatalysts have been developed, including metal oxides (TiO 2 , Bi 2 O 3 , etc), 13‐16 metal sulfides (MoS 2 , Bi 2 S 3 , etc), 17‐21 multi‐component oxides (Bi 2 WO 6 , SrTiO 3 , etc), 22‐25 metal selenides (MoSe 2 , CdSe, etc), 26‐29 metal phosphides (Co 2 P, Ni 2 P, etc), 30‐32 metal phosphates (Ag 3 PO 4 , BiPO 4 , etc), 33,34 metal halides (AgBr, etc), 35‐37 metal oxyhalides (BiOBr, BiOCl, etc), 38‐40 metal‐free materials (SiC, g‐C 3 N 4 , etc) 41‐43 and so on. Among them, the semiconductor with a band gap of Eg ≥ 3 eV are called wide‐band‐gap photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, BiOCl will form directly from Bi 2 O 3 , e − and ˙Cl radical as shown in eqn (14). 61 After the wastewater treatment, Bi 2 O 3 is regenerated from BiOCl using sodium hydroxide (NaOH) solution as shown in eqn (15). As a result, Cl(−I) is ultimately transferred from the wastewater to the sodium chloride/ sodium hydroxide (NaCl/NaOH) concentrate.…”
Section: Uv-induced Oxidation Methodsmentioning
confidence: 99%
“…After further treatment on BiOCl using NaOH solution, approximately 97.4% of Bi 2 O 3 was regenerated and reused in the next batch of Cl(−I)-removal experiments. 61 Because of the addition of UV light, the mole ratio of dosed Bi 2 O 3 to Cl(−I) was lowered from 1.5 : 1 to 0.5 : 1. Meanwhile, the required initial H 2 SO 4 concentration of the wastewater was also lowered from 70 to 40 g L −1 , signifying that the traditional Bi 2 O 3 precipitation method has been significantly improved.…”
Section: Oxidation-removal Methods Of Cl(−i)mentioning
confidence: 99%
“…32,44 However, no obvious signals for the •Cl radical can be observed in the ESR spectra, which was speculated to be caused by the extremely fast reaction rate of the •Cl radical. 17,18 In this method to remove Cl(−I) using PS, the advanced oxidation reactions by the •OH and •SO 4 − radicals were the major oxidation paths for Cl(−I), whether under dark or UV light conditions. The contribution ratio of •OH and •SO 4 − radicals for the removal of Cl(−I) by PS was 28.3% and 71.7%, respectively.…”
Section: Product For the Removal Of Cl(−i) By Pms Or Psmentioning
confidence: 99%
“…15,16 In our previous studies, to solve the high reagent dosage and low efficiency problems in the above precipitation methods, ultraviolet (UV) light was adopted to improve the removal process of Cl(−I). 17,18 It was found that in the UV/Cu/Cu 2+ and UV/Bi 2 O 3 methods, the hydroxyl (•OH) radical played an important role in the oxidation removal of Cl(−I), leading to enhanced efficiency and decreased reagent dosage. The successful oxidation of Cl(−I) by •OH radical provided a new idea of the advanced oxidation process (AOP) as a potential approach for the removal of Cl(−I) from wastewater.…”
Section: Introductionmentioning
confidence: 99%